Artificial Intelligence and the Constitutional Court: A Newpath of Making Independent Decisions? - Vicko Taniady; Steven Theonald Siahaan (Jurnal Kajian Pembaruan Hukum, 2023)
The Constitutional Court is facing problems because many decisions are not in favor of the community and are not independent. The constitutional judges are sometimes not independent, as in cases of corruption, and there are indications of a change in the substance of the decision. This study aims to analyze how the procedures for constitutional judges make decisions, and then the authors relate it to the urgency of implementing AI in helping judges make decisions. The research method used is doctrinal and socio-legal. This research uses literature study techniques to obtain secondary data. The study results show that constitutional judges' existence is essential in maintaining the rule of law and democracy in Indonesia today. So, to face the problems today, AI is needed. AI is expected to assist constitutional judges in making decisions, document review, and predictive analysis. The application of AI has been carried out by many countries, which have succeeded in helping judges make decisions. However, several challenges must be prepared, such as the need for regular AI inspections, supervision of the use of AI by the Constitutional Court Honorary Council and the independent Constitutional Court technicians, and the need for a legal umbrella for the application of AI within the Constitutional Court.